EFFECT OF HEAT STRESS ON OVARIES EVOLUTION OF REPEAT BREEDERS IN DAIRY CATTLE, SPECIFICALLY HOLSTEIN FRIESIAN - TARIQ, M; KHAN, M; MANZOOR, H; ASGHAR, MA; NAZEER, HAA; SADIQ, AB; SHAH, SH; RAUF, U; ZEB, K; REHMAN, MU (Biological and Clinical Sciences Research Journal, 2024)
The reproductive performance of dairy cattle, particularly Holstein Friesian breeds, is crucial in herd productivity and profitability. The study’s main objective is to find the effect of heat stress on the evolution of ovaries of repeat breeders in dairy cattle, specifically Holstein Friesian. An exploratory study was carried out on various commercial dairy farms in Faisalabad, Pakistan, during the peak summer months May 2023 to July 2023, to investigate the influence of heat stress on ovarian function and the evolution of repeat breeders in Holstein Friesian dairy cattle. 500 Holstein Friesian dairy cattle were selected from multiple commercial dairy farms for experiencing heat stress. Cattle were chosen based on age, parity, and reproductive history to ensure representation of the target population. Data were collected from 500 cattle to measure the heat stress. Heat-stressed cows exhibited a higher proportion of follicles sized below 5mm (45%) compared to thermoneutral cows (20%), while thermoneutral cows showed a greater percentage of follicles sized between 5-10mm (50% vs. 35%). Heat-stressed cows exhibited a higher prevalence of follicular cysts (25%) compared to thermoneutral cows (10%), along with a greater incidence of corpus luteum persistence (40% vs. 20%). Heat-stressed cows displayed lower estrous detection rates (50%) compared to thermoneutral cows (70%), along with reduced conception rates per estrus (20% vs. 40%) and pregnancy rates per artificial insemination (AI) (15% vs. 35%). It is concluded that heat stress significantly affects ovarian function and is associated with the evolution of repeat breeders in Holstein Friesian dairy cattle. The higher prevalence of follicular cysts, corpus luteum persistence, and granulosa cell apoptosis observed under heat stress conditions contributes to compromised reproductive performance and increased incidence of repeat breeding.